Legalization of Prostitution: A Review of the Sri Lankan Context with Comparative Analysis - Amarasinghe, Kusal (VidhiAagaz, 2023)
There are two dimensions of this study. The first one is to identify the factors regarding prostitution with different perspectives and the second one is to understand how the different jurisdictions have legalized the sex industry. The core objective of this research is to analyse these two dimensions and diagnose how Sri Lankan society recognize prostitution. To address the first dimension of this study, the researcher analysis legal, social, and medical perspectives regarding the sex industry in Sri Lanka. In accordance to fulfill this objective, data was gathered by interviewing five different stakeholders with a customized analytical approach. For this part of the study, the researcher has collected qualitative data. Regarding the second dimension of the study, the researcher comparatively analyses the legality of prostitution in different jurisdictions. For this analysis, the researcher has selected six regions globally. The study further analyses the domestic legal framework, and social and medical perspectives regarding prostitution. Therefore, this research can be identified as a comprehensive analysis of prostitution in Sri Lanka.
Keywords: Brothels; Prostitution; Sex; Industry; STD